Securities for bankers advances in Malaysia / Siti Nor Husin - Husin, Siti Nor (Faculty of Law, 1984)
The question of Banker’s securities becomes important in the course of a bank's lending operation. Before a loan can be advanced by a bank, a bank must satisfy itself that repayment would be made within the period specified. And that in the event of any default by the borrower, recourse can be had either against property or person to realize any outstanding amount. Securities are in fact, a kind of insurance against default in payment of a loan or interest or when the loan is regarded as bad. The legal requirements relating to bankers securities as well as requirement as to their documentation must be stringently observed. This need to be done to ensure that no problems will arise in relation to the enforcement of the securities later on.